Comparing plaque removal efficacy of biodegradable toothbrush and nonbiodegradable toothbrush in children of 8-10 years of age: A randomized clinical study - Pratik B. Kariya; Arohi Desai; Sweta Singh; Barkha Bansal; Yash Shah (Wolters Kluwer Medknow Publications, 2024)
Introduction: In the 21st century, we are surrounded by plastic, disposal of which has a detrimental effect on the environment. Around 700 million plastic toothbrushes are sold which contributes to a large portion of plastic waste. To aid in the restoration of the environment, there is a need to replace plastic toothbrushes with recyclable toothbrushes. The purpose of the study was to evaluate and compare the plaque removal efficacy of biodegradable toothbrushes and nonbiodegradable toothbrushes in children 8-10 years of age. Methodology: Ninety children 8-10 years old from school were included in the study. Toothbrush types to groups A (nonbiodegradable toothbrush, Colgate® Palmolive India Ltd.), B (Biodegradable toothbrush, Bamboo India), and C (Biodegradable toothbrush, Palette™ India) were randomly allocated and plaque score was evaluated using plaque disclosing agent and Turesky Modification of Quigley Hein Index at day 1, 7, and 14. The data were analyzed using unpaired "t" and analysis of variance to find the significance of study parameters between the groups and paired t-test was used to find the significance of study parameters within the group (pre- and postbrushing). Results: The comparison of plaque scores pre- and postbrushing in all groups manifested reduction from day 1 to 14. However, Group B showed a significant reduction of plaque on day 14 with a difference of 0.50 which is statistically significant with a P < 0.001. Conclusion: According to the results, it can be concluded that a biodegradable toothbrush has adequate plaque removal efficacy. Therefore, the use of biodegradable toothbrushes can be recommended which will reduce nonbiodegradable waste.